Analysis of mechanical properties engine-driven NiTi instruments with different thermally treated - Klymus, Michel Espinosa (2021)
Objective: article 1- The aim of this study was to evaluate the impact of body temperature on the cyclic fatigue resistance of different NiTi alloys used for the manufacturing of Reciproc Blue R25 (RB 25.08; VDW, Munich, Germany), X1 Blue File 25 (X1 25.06; MK Life Medical and Dental Products, Porto Alegre, Brazil) and WaveOne Gold Primary (WOG 25.07; Dentsply Maillefer, Ballaigues, Switzerland). Article 2- evaluate the cyclic and torsional fatigue resistance of Nickel-Titanium rotary instruments with similar cross sectional design and manufactured by different thermal treatments. Methodology Article 1- Sixty instruments of the RB 25.08, X1 25.06 and WOG 25.07 systems were used (n = 20). Cyclic fatigue tests were performed at room temperature (20° ± 1 °C) and at body temperature (37° ± 1 °C). The instruments were reciprocated until fracture occurred in a stainless steel artificial canal with a 60° angle and a 5-mm radius of curvature. The time to fracture (TTF) was recorded. Also, the number of cycles to fracture (NCF) was calculated. Data were analysed using one-way ANOVA and Tukeys tests for inter-group comparison at both temperatures and for the reduction of cyclic fatigue at body temperature. For intra-group comparison at the different temperatures, the unpaired t test was used. Article 2- eighty instruments of Hyflex CM (HCM; #25/.06) Vortex Blue (VB; #25/.06), Sequence Rotary File (SRF; #25/.06) and EdgeSequel (EDF #25/.06) were used (n=20). Cyclic fatigue test evaluated the time and number of cycles to failure (NCF) in a stainless steel artificial canal with 60° and 5-mm radius of curvature (n=10). The torsional test (ISO 3630-1) evaluated the maximum torque and distortion angle to failure in the 3 mm from the tip (n=10). The topographic features of fractured surface of instruments were assessed using scanning electron microscopy (SEM). Data were analyzed using one-way ANOVA and Tukey tests, and the level of significance was set at 5%.Results: Article 1- The cyclic fatigue test at 20 °C showed that RB 25.08 and X1 25.06 presented significantly higher TTF and NCF than WOG 25.07 (P < 0.05). At 37 °C, all groups presented significant reduction of TTF and NCF (P < 0.05). RB 25.08 presented significant higher TTF than WOG 25.07 (P < 0.05). Regarding the NCF, there was no significant difference among the groups (P > 0.05). The WOG 25.07 presented the lowest percentage reduction of cyclic fatigue (P < 0.05). Article2- The HCM presentedthe longest time and highest NCF to cyclic fatigue compared with all the groups (P<0.05). The SRF presented similar time as, (P<0.05) and lower NCF (P<0.05) to fatigue than VB. Relative to the torsional test, HCM presented the lowest torque load and the highest distortion angleof all the groups(P<0.05). The SRF and EDF presented similar torque load (P>0.05). There was no difference among VB, SRF and EDF regarding the distortion angle (P>0.05). The SEM analysis showed typical features of cyclic and torsional fatigue for all instruments tested. Conclusion: Article 1- The body temperature treatment caused a marked reduction of the cyclic fatigue resistance for all reciprocating instruments tested. The RB 25.08 and X1 25.06 systems presented similar results at both temperatures tested. However, WOG 25.07 presented the lowest percentage reduction in fatigue resistance at body temperature. Clinical relevance Cyclic fatigue resistance of NiTi reciprocating instruments has been evaluated at room temperature. However, the fatigue resistance significantly decreases upon exposure to body temperature, which could affect the mechanical behaviour of the NiTi instruments during root canal preparation. Article 2- The HCM presented the highest cyclic fatigue resistance and angular rotation to failure. However, the VB showed higher torsional strength to failure.